The Interplay between Fear of Cancer Recurrence and Unmet Needs in Breast Cancer Survivors – A Systematic Review - Puji Astuti; Yati Afiyanti; Riri Maria (Indonesian Journal of Global Health Research, 2026)
Advances in early detection and treatment have improved breast cancer survival rates; However, survivors often face psychosocial challenges such as Fear of Cancer Recurrence (FCR) and unmet needs. FCR refers to anxiety or worry about cancer returning, while unmet needs represent the gap between the support required and that received—particularly in emotional and informational aspects. Understanding their interplay is vital for developing comprehensive, needs-based nursing interventions. This study aimed to systematically review the relationship between FCR and unmet needs among breast cancer survivors, focusing on prevalence, contributing factors, and their impact on quality of life and health-related behaviors such as screening adherence and healthcare utilization. A systematic search was conducted across PubMed, Scopus, and ProQuest using the keywords “fear of cancer recurrence,” “unmet needs,” and “breast cancer survivors.” Articles written in English with systematic reviews, cross-sectional, cohort, qualitative, or mixed-methods designs were included. From 1,414 identified studies, eight met inclusion criteria and were analyzed qualitatively following PRISMA guidelines. Moderate to high FCR levels were found in 50–70% of survivors, and 60–70% reported at least one unmet need, mainly emotional and informational. Higher FCR levels were strongly associated with increased unmet needs. Unmet needs mediated FCR's impact on health behaviors, leading to lower screening participation and higher unplanned healthcare use. Younger age, comorbidities, and low social support exacerbated both factors. FCR and unmet needs are interrelated psychosocial issues affecting survivors' emotional well-being and behavior. Oncology nursing should integrate structured assessments and tailored interventions to improve survivors' quality of life.